Need Analysis of Mobile Learning Based on Problem Based Learning for Elementary School Student - Yarmi, Gusti; Suntari, Yustia; Usman, Herlina; Yesi, Yesi (JTP - Jurnal Teknologi Pendidikan, 2024)
Critical thinking skills of elementary school students still need to be considered again, especially in learning Social Studies. One way to improve students' critical thinking skills is by using Mobile Learning Social Studies learning media. This study aims to determine the needs analysis in developing Mobile Learning based on Problem-Based Learning in learning Social Studies in Elementary Schools where the products developed are expected to be able to improve students' critical thinking skills. The research was conducted at East Jakarta Elementary School with 30 students as research subjects. The research method used is Research and Development using the ADDIE approach including Analysis, Design, Development, implementation and evaluation. However, the implementation in this research only conducts the analysis stage to determine the analysis of student and teacher needs to develop mobile learning social studies products according to field needs. Data collection techniques used are observation, interviews and questionnaires. The results of this study are that the learning media used during learning still do not pay attention to the characteristics of students and the development of 21st century learning and learning models that are still fixated on classical learning models so that the development of PBL-based mobile learning media is needed.